2020
DOI: 10.2478/helm-2020-0018
|View full text |Cite
|
Sign up to set email alerts
|

Soil and sand contamination with canine intestinal parasite eggs as a risk factor for human health in public parks in Niš (Serbia)

Abstract: SummaryRegarding geographical distribution and clinical relevance, the most common canine geohelminths are Toxocara canis, ancylostomatids, and Trichuris vulpis. Canine intestinal parasites from the soil and sand present an important potential serious human health hazard, especially for the children preschool and school – age. This paper aimed to establish the degree of contamination of soil and sand with zoonotic parasites from the canine feces and the degree of risk they could pose for human health in public… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 28 publications
0
11
0
3
Order By: Relevance
“…Along with this, it was found that under the conditions of the canine center, the source of environmental pollution by exogenous forms of helminths T. canis is the fly Musca domestica L. (Paliy et al, 2018b). 26% of sand samples contaminated with T. canis helminths were identified (Ristić et al, 2020).…”
Section: Introductionmentioning
confidence: 85%
“…Along with this, it was found that under the conditions of the canine center, the source of environmental pollution by exogenous forms of helminths T. canis is the fly Musca domestica L. (Paliy et al, 2018b). 26% of sand samples contaminated with T. canis helminths were identified (Ristić et al, 2020).…”
Section: Introductionmentioning
confidence: 85%
“…degree of contamination was detected in soil samples (4-12%). T. canis (26%) and Alaria alata (16%) eggs contamination was found in the sand samples (Ristic et al, 2020). According to the results of testing faecal samples of dogs kept by owners outside their homes in Bulgaria, the overall prevalence of parasites in the gastrointestinal tract was 64.5%.…”
Section: Introductionmentioning
confidence: 97%
“…Trichuris vulpis (Froelich, 1789) and Toxocara canis (Werner, 1782) are parasitic nematodes, the definitive hosts of which are dogs and members of the Canine family. Both parasites are geohelminths, their eggs mature in the environment, maintaining viability for a long time due to the special structure of the shells (Abou-El-Naga, 2018;Bojar & Klapec, 2018;Borodai & Hodyna, 2019;Marko et al, 2020;Ristic et al, 2020). According to the results of scientific research, the geography of biohelminth distribution centres is usually more extensive, even despite the binding of intermediate nutrients to certain living conditions (Boyko & Brygadyrenko, 2017;Zazharska et al, 2018;Feshchenko et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In Serbia, several studies related to the presence of zoonotic nematodes in wild carnivores (Ilić et al, 2016a;2016b;Hadži-Milić et al, 2016;Gajić et al, 2019), nonowner dogs (Ristić et al, 2020a;2020b), shelters dogs (Ilić et al, 2021), and owned dogs and cats (Ilić et al, 2017;Ristić et al, 2020a;Stepanović et al, 2021) have been reported, while those related to carnivorous filariasis are of special importance (Tasić et al, 2008;Tasić et al, 2012;Penezić et al, 2014;Stepanović et al, 2015;Gavrilović et al, 2015;Kurucz et al, 2016).…”
Section: Introductionmentioning
confidence: 99%